Modified Phenol/Chloroform‐Free DNA Isolation from Yeast and Other Fungi by Non‐Enzymatic Salting Out Method. Issue 4 (25th April 2023) - Bandehpour, Mojgan; Dehghani, Niloofar; Jaliani, Hossein Zarei; Asadi‐saghandi, Abolghasem
Abstract: The most commonly used fungal DNA extraction techniques require enzymatic digestion or hazardous chemicals. Here, we describe a quick non‐enzymatic salt‐out method that we developed for isolating high‐quality DNA from various fungal species. DNA was extracted from four species of typical fungi, including Saccharomyces cerevisiae, Hansenula polymorpha, Candida albicans, and Aspergillus flavus . Results that we obtained from agarose gel electrophoresis and spectrophotometry verified the integrity, high quality, and purity of the extracted DNAs. Also, PCR amplification and restriction enzyme digestion confirmed the efficiency of the extracted DNAs in molecular biology applications. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Yeast and fungal cultivation for DNA extraction Basic Protocol 2 : Modified salting out DNA extraction protocol Support Protocol 1 : PCR amplification of extracted genomes Support Protocol 2 : Digestion with restriction enzyme